Self‐assembly properties of ultra‐long‐chain gemini surfactant with high performance in a fracturing fluid application. Issue 11 (17th November 2016) - Yang, Chunpeng; Hu, Zhiyuan; Song, Zhaozheng; Bai, Jianyong; Zhang, Yuan; Luo, JiaQing; Du, Yongxin; Jiang, Qingzhe
ABSTRACT: A new cationic gemini surfactant (C25‐6‐C25), which had a special structure consisting of ultra‐long hydrophobic chains and amide groups, was synthesized using a main feedstock source obtained from rapeseed for thickening purposes. The 12 mmol L −1 C25‐6‐C25 fluid containing 0.19 mol L −1 potassium chloride (KCl) exhibited highly elastic properties at the angular frequency of 0.04–10 rad s −1 . Its viscosity could be maintained at 55 mPa s for 1.5 h under a shear rate of 170 s −1 at 110 °C and it also showed a good proppant‐suspending property. C25‐6‐C25/KCl fluid exhibited high viscoelasticity and good performance, which were attributed to intermolecular forces, hydrogen bonding, and the shielding effect of electrostatic repulsion by KCl. Thus, C25‐6‐C25 is a very promising candidate for fracturing. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44602. Abstract :